Analysis of Factors Influencing The Increase in Caesarean Section Delivery Choices at Permata Hati Hospital In Kisaran in 2024 - Nur Astari; Chrismis Novalinda Ginting; Ali Napiah (Green Publisher Indonesia, 2025)
Every woman wants her birth process to run smoothly and normally. The birth process can be normal (normal parturition), but there are also birth processes that have problems so that an operation called a caesarean section is required. In the past and to this day, sectio caerasea is a scary procedure. But currently the number of cesarean sections is increasing and there are even pregnant women who want to give birth by surgery. The aim of this study was to analyze the factors that influence the increase in the choice of caesarean section delivery at Permata Hati Kisaran Hospital in 2024. Quantitative type of research and cross-sectional design. The sample for this study was 83 women giving birth at Permata Hati Kisaran Hospital using the chi square test and multiple logistic regression analysis. The results of this study show that the most dominant variable is complications during pregnancy (p= 0.00; Exp(B)=31.3). It is recommended that women giving birth with pregnancy complications for both mother and baby should decide on caesarean section because caesarean section be a decision taken immediately due to an emergency situation. So that pregnant women can avoid complications during pregnancy and childbirth later and it is recommended that midwifery staff carry out more precise anamnesis and examinations of pregnant women because this will have an impact on the type of delivery.